Enhanced thermo-hydraulic performance in a V-ribbed triangular duct solar air heater: CFD and exergy analysis. (1st June 2020) - Nidhul, Kottayat; Kumar, Sachin; Yadav, Ajay Kumar; Anish, S.
Abstract: Computational fluid dynamics (CFD) and exergy analysis are conducted to investigate the impact of secondary flow produced by V-ribs on the overall performance of a triangular solar air heater (SAH) duct. For a fixed relative rib pitch ( R p  = 10) and relative rib height ( R h  = 0.05), the effect of rib inclination ( α ) is studied using CFD technique for varying Reynolds number (5000 ≤ Re  ≤ 20000). Based on the CFD simulation results, empirical correlations capable of predicting Nu and f with an absolute variance of 8.7%, and 4.7%, respectively, are developed. Employing these correlations, exergetic performance analysis is carried out. Maximum effectiveness parameter ( ε ) of 2.01 is obtained for α  = 45° at Re  = 7500. The exergy analysis reveals that the entropy generated is lower for the ribbed triangular duct compared to the smooth duct with maximum enhancement in exergetic efficiency ( η ex ) as 23% for α  = 45°. The study is extended for the rectangular duct to compare the performance with the ribbed triangular duct SAH ( α  = 45°). Results show that ribbed triangular duct SAH ( α  = 45°) is superior over various configurations of the ribbed rectangular duct SAH at higher mass flow rates. Highlights: CFD and exergy analysis of a triangular duct solar air heater with V-rib is proposed. Secondary flow in triangular duct significantly enhances the Nusselt number. A significant enhancement in the effectiveness parameter of 2.01 is obtained. Empirical correlations are developed for Nusselt number and friction factor. The proposed design exhibits superior performance at high mass flow rates.